Therapeutic targets for venous thromboemblism: proteome-wide mendelian randomization and colocalization analyses - Xiaolong Li; Cheng-hao Yang; Min Zhou; Min-yi Yin (Thrombosis Journal)
Abstract Background Venous thromboembolism (VTE) is a significant global health issue, yet effective therapeutic targets for its prevention and treatment remain elusive. This study aimed to identify plasma proteins causally associated with VTE risk using proteome-wide Mendelian randomization (MR) and colocalization analyses. Methods We utilized genome-wide association study (GWAS) data from the UK Biobank and FinnGen cohorts, encompassing 38,573 VTE cases and 946,373 controls. Plasma protein levels were quantified using Olink technology in the UK Biobank Pharma Proteomics Project (UKB-PPP) and SomaScan in the deCODE Health study. MR analysis was performed to assess causal relationships, followed by colocalization analysis to evaluate shared genetic variants. Functional enrichment analyses and molecular docking were conducted to explore biological mechanisms and predict potential therapeutic compounds. Results Eight proteins showed significant associations with VTE risk after Bonferroni correction (p < 3.19 × 10−5). Odds ratios ranged from 0.98 (95% CI: 0.98–0.99) for PLEK to 1.03 (95% CI: 1.02–1.04) for LRP12. Strong colocalization evidence (PH4 ≥ 0.8) was found for LRP12, F11, PLCG2, and ABO. Molecular docking identified promising drug candidates including valine, folic acid, ibrutinib, and simvastatin, with valine showing the strongest binding energy (-32.057 kcal/mol). Conclusions This study highlights novel therapeutic targets for VTE and provides insights into potential drug candidates. These findings offer a foundation for future research and drug development aimed at reducing VTE risk.